Implementasi Analytical Hierarchy Process pada Penetapan Hakim di Pengadilan Negeri Malang - Herlina Devi Sirait; Nurul Hidayat; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The judge is an official who can try in a court of law in a country. Every day the head of the court makes a judge's decision to handle cases of various types and classifications. Cases that are registered by the plaintiff for each day have an average of 8 to 10 cases and for each week 35 to 40 cases. Whereas the judge's appointment time is quite short, which is a maximum of 3 days and at least 1 day. The head of the court experienced a difficulty in making a judge's decision because of the fairly short amount and timing of the stipulation. Then a system is needed that hopes to help the effectiveness of the selection of a judge so that the determination of the judge is faster and does not exceed the predetermined time limit. The method used in determining this judge is the Analytical Hierarchy Process. The criteria used are leadership, cases handled, and length of decision. Each criterion has sub-criteria, namely: cases handled have the same type and classification sub-criteria, different types but the same classification, different types and classifications. The length of the verdict has sub-criteria is not good, the decision is long enough, long the decision is good, and the decision is very good for a long time. Leadership has sub-criteria of chairpersons, member judges, and single judges. The system output results in 5 alternative order judges with the highest to lowest values. Spearman rank correlation method as a method of testing the results of the system with results from experts. From the tests that have been done, it is obtained a correlation value of 0.646, the value means that the correlation obtained from the comparison of system results and experts is a strong correlation.